Mature teratoma containing carcinoid tumour arising within a fallopian tube. Issue 3 (31st March 2019) - Preshaw, Jessica; Sherpa, Toshi; Pawade, Joya; Vyas, Sanjay
Abstract : A 52-year-old woman with a background of vaginal hysterectomy for heavy menstrual bleeding underwent an elective laparoscopic adhesiolysis, left salpingo-oophorectomy for left-sided pelvic pain, and a right salpingectomy. Despite a grossly normal appearance, histology revealed a rare presentation of mature teratoma with insular carcinoid tumour arising from the left fallopian tube. Even though the salpingectomy was thought to be curative, the patient underwent a second operation to remove her remaining right ovary as a precaution against malignant spread. In light of limited information in such rare cases, counselling on best management and discussion of risks to guide patient decision making remains challenging.